2016
DOI: 10.1007/s00213-015-4193-6
|View full text |Cite
|
Sign up to set email alerts
|

Mad men, women and steroid cocktails: a review of the impact of sex and other factors on anabolic androgenic steroids effects on affective behaviors

Abstract: Rationale For several decades, elite athletes and a growing number of recreational consumers have used anabolic androgenic steroids (AAS) as performance enhancing drugs. Despite mounting evidence that illicit use of these synthetic steroids has detrimental effects on affective states, information available on sex-specific actions of these drugs is lacking. Objectives The focus of this review is to assess information to date on the importance of sex and its interaction with other environmental factors on affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 301 publications
(344 reference statements)
0
20
0
1
Order By: Relevance
“…Due to the increase in the number of AAS users and by the effects on mental and physical health [16,17,18], there is an increasing need for studying these substances. The present work aimed to bring more knowledge regarding the effect of two widely used anabolic-androgenic steroids in six different areas of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increase in the number of AAS users and by the effects on mental and physical health [16,17,18], there is an increasing need for studying these substances. The present work aimed to bring more knowledge regarding the effect of two widely used anabolic-androgenic steroids in six different areas of the brain.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Masculinizing hormones have been associated with a possible destabilization of psychotic and bipolar disorders, especially with supraphysiological blood levels of testosterone 7 in both cisgender and transgender men. 105–106 The likelihood of such episodes can, therefore, be minimized by careful dosing and monitoring.…”
Section: Mental Health Assessment and Treatmentmentioning
confidence: 99%
“…AAS use can suppress pituitary LH and FSH secretion, leading to menstrual irregularities and even infertility. Also, in some studies, female athletes reported increased aggressiveness with the use of steroids (70). Dyslipidemia, hypertension, arrhythmia, coagulation disorders, fibrosis, and cardiac hypertrophy have been observed (71,72).…”
Section: Testosterone Misuse and Abusementioning
confidence: 99%